Oddziaływania tyflomuzykoterapeutyczne wspierające rozwój ruchowy dziecka z niepełnosprawnością wzroku - CYLULKO, PAWEŁ (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Paweł Cylulko, Oddziaływania tyflomuzykoterapeutyczne wspierające rozwój ruchowy dziecka z niepełnosprawnością wzroku [Typhlo music therapy interventions that facilitate motor development of visually impaired children]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 153-30. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.09 The article discusses the possibilities of using music therapy to facilitate motor development of children with visual impairments. Cognitive functioning of children without vision implies certain psychophysiological, emotional and social problems, including substantial delay in motor development in comparison to non-impaired peers. Thanks to the integration of music with various forms of movement and the sonic and musical interaction between a music therapist and a child, it is possible to reduce the child’s psychomotor delay, and improve their orientation and locomotion in small and large spaces. The author, musician, teacher and music therapist, shares his observations and experiences gained during almost thirty years of work with children at the Maria Grzegorzewska Lower Silesian Special Educational Centre No. 13 for the Blind and the Visually Impaired in Wrocław.